2019
DOI: 10.1177/0022167819844071
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Veteran Identity Through Community Engagement: A Chaplain–Psychologist Collaboration to Address Moral Injury

Abstract: Moral injury (MI) is gaining traction within the Department of Veterans Affairs (VA) as an essential construct for understanding an important dimension of suffering experienced by U.S. combat-deployed Veterans. A VA chaplain and a psychologist at the Corporal Michael J. Crescenz VA Medical Center in Philadelphia co-facilitate a 12-week Moral Injury Group (MIG) to provide education about MI, the collective responsibility for the consequences of warfare, and related topics. A Community Ceremony in the VA chapel,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 41 publications
0
47
0
Order By: Relevance
“…The framework of the MIG intervention has been described in detail previously (Antal et al., 2019). Briefly, the development and framework of the MIG intervention were informed by theoretical models (Antal & Winings, 2015; Litz et al., 2009; Tick, 2005, 2014), recommendations later summarized (Griffin et al., 2019), and case study implementation (Antal et al., 2019). The weekly outpatient MIG session provides educational information about moral injury and explores related topics, such as moral emotions, moral values, moral dilemmas, and moral disengagement.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The framework of the MIG intervention has been described in detail previously (Antal et al., 2019). Briefly, the development and framework of the MIG intervention were informed by theoretical models (Antal & Winings, 2015; Litz et al., 2009; Tick, 2005, 2014), recommendations later summarized (Griffin et al., 2019), and case study implementation (Antal et al., 2019). The weekly outpatient MIG session provides educational information about moral injury and explores related topics, such as moral emotions, moral values, moral dilemmas, and moral disengagement.…”
Section: Methodsmentioning
confidence: 99%
“…Even the symptoms that overlap can diverge in their conceptual implications. For example, symptoms of guilt, shame, and anger may be treated as pathological in conceptualizations of PTSD, yet they can also be framed as normal and even healthy responses to a morally injurious experience (Antal et al., 2019). Investigators have also found potential differences in brain mechanisms with regard to PTSD and moral injury.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The Special Issue expresses a wide range of veteran community engagement and collaboration strategies. These areas include (1) arts-based efforts using theater as a treatment for posttraumatic stress disorder (Ali et al, 2019); (2) engaging with military veteran college students in higher education settings (Dobson et al, 2019; Kent & Buechner, 2019); (3) addressing changes in veteran identity in the aftermath of moral injury and integrations between the chaplaincy and psychology (Antal, et al, 2019); (4) activating multisector coalitions in the United States and Canada for collective impact on veterans issues at the community level (Fewster et al, 2019; this foreword); (5) veteran volunteering as a reintegration strategy in civilian life (Matthieu et al, 2019); (6) examining the experiences of military nurses during and after the Korean War as a reflection on country building and the formalization of nursing as profession in both Korea and the United States (Jun et al, 2019); (7) veteran collaboratively designed mindfulness classes in the VA setting (Uebel); (8) engaging veterans in advisory roles with VA health services research (Wendleton et al, 2019); (9) using photovoice as a strategy to increase trust and communication between veterans larger institutions (True et al, 2019); (10) collaborative research on veteran homelessness issues (Nelson et al, 2019); (11) exploring the lived experiences of recent military veterans using psychedelics as a strategy for self-medication (Hooyer, 2020); (12) and engaged strategies for ecological momentary assessment research of alcohol use among veterans in a community based peer support program (Hall et al, 2019); (13) faith-based coalitions to support veteran reintegration hubs (Bennet, et al); and (14) collaborative design of veteran peer support training curricula (Ruffalo, et al, (in press)).…”
Section: Walking the Talk: Collaboratively Building This Special Issuementioning
confidence: 99%